A Pregnant Patient With a Large Anterior Mediastinal Mass for Thymectomy Requiring One-Lung Anesthesia. (March 2021) - Ho, Anthony M.-H.; Pang, Etonia; Wan, Innes P. W.; Yeung, Eugene; Wan, Song; Mizubuti, Glenio B.
Anesthetic management for anterior mediastinal mass resection is often challenging. The main concern being that the tumor might, on reduction in muscle tone, cause circulatory and/or airway collapse. In the setting of pregnancy, the expected physiologic changes (eg, increased oxygen demand, decreased functional residual capacity, and aortocaval compression) may further increase the risks. The objective of this report is to present a challenging case of a pregnant woman undergoing an anterior mediastinal mass resection with the additional rare requirement for one-lung anesthesia, and to describe the perioperative considerations and the plan executed to ensure a successful outcome. A 30-year-old pregnant (23 weeks) patient with a large anterior mediastinal mass and evidence of significant cardiovascular and tracheobronchial compression presented for thymectomy requiring one-lung ventilation. Anesthesia consisted of preoperative preparation, thoughtful selection of vascular access sites, preservation of spontaneous ventilation until sternotomy was accomplished, use of bronchial blocker and readily reversible pharmacologic agents, availability of backup airway and oxygenation plans, standby high-frequency ventilation, and anticipation of postoperative respiratory difficulties. Surgical considerations included the possibility of extracorporeal membrane oxygenation and the need for lifting the thymoma to relieve the compression of the mediastinum. A methodical and multidisciplinary plan is described to mitigate the risk of cardiorespiratory collapse in the setting of anterior mediastinal mass resection. Backup measures in case of catastrophe, as well as careful consideration of the physiologic changes of pregnancy, must be taken into account.